MORPHOLOGICAL AND SYNTACTICAL ERRORS ANALYSIS ON STUDENTS WRITING SKILL AT PAMULANG UNIVERSITY, SOUTH TANGERANG, BANTEN - Kholil Azis (Universitas Pamulang, 2021)
The aim of this research is to find out the Morphological and Syntactical errors made by the students in their written texts, the number of errors, and the types of errors that most often appear. The method which is used in this research is descriptive method. Descriptive research method refers to the method used to describe the data and the characteristics used to describe the population. The purpose of using the descriptive method is to obtain systematic, factual and accurate data that can provide an actual picture of the data that is the research material. Descriptive research methods should not be used in making causal relationships where one variable affects other variables. The source of the data was taken from the writings of 10 first semester students of the Faculty of Letters, Pamulang University, South Tangerang, Banten. In collecting data, the students were asked to write an essay in English. Students are given the freedom of topics to be written. In conclusion, from the 69 errors identified, there were 13 errors in the Morphological category and there were 56 errors in the Syntactical category from the total data found. From these results, it can be concluded that students make greater mistakes in the Syntactical category.